Expression of p53 Target Genes in the Early Phase of Long-Term Potentiation in the Rat Hippocampal CA1 Area. (12th February 2015) - Pustylnyak, Vladimir O.; Lisachev, Pavel D.; Shtark, Mark B.
Abstract : Gene expression plays an important role in the mechanisms of long-term potentiation (LTP), which is a widely accepted experimental model of synaptic plasticity. We have studied the expression of at least 50 genes that are transcriptionally regulated by p53, as well as other genes that are related to p53-dependent processes, in the early phase of LTP. Within 30 min after Schaffer collaterals (SC) tetanization, increases in the mRNA and protein levels of Bax, which are upregulated by p53, and a decrease in the mRNA and protein levels of Bcl2, which are downregulated by p53, were observed. The inhibition of Mdm2 by nutlin-3 increased the basal p53 protein level and rescued its tetanization-induced depletion, which suggested the involvement of Mdm2 in the control over p53 during LTP. Furthermore, nutlin-3 caused an increase in the basal expression of Bax and a decrease in the basal expression of Bcl2, whereas tetanization-induced changes in their expression were occluded. These results support the hypothesis that p53 may be involved in transcriptional regulation during the early phase of LTP. We hope that the presented data may aid in the understanding of the contribution of p53 and related genes in the processes that are associated with synaptic plasticity.